1998
DOI: 10.1017/s0022215100140514
|View full text |Cite
|
Sign up to set email alerts
|

Ortner's syndrome revisited

Abstract: Hoarseness of voice due to paralysis of the left recurrent laryngeal nerve caused by a dilated left atrium in mitral stenosis as discussed by Ortner, is a subject of controversy. Different authors have cited different mechanisms as explanation. A variety of cardiac problems such as primary pulmonary hypertension, ischaemic heart disease, various congenital heart disorders can all lead to paralysis of the left recurrent laryngeal nerve. Most authors believe that pressure in the pulmonary artery causes the nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 7 publications
0
22
0
1
Order By: Relevance
“…3,4 It was also associated with double outlet right ventricle, 5 Ebstein's anomaly, 6 patent ductus arteriosus (PDA), 7 and Eisenmenger's complex. 8 Ductal ligation and transcatheter closure of PDA is associated with a risk of LRLN palsy. 9,10 Infants, who are less than 1500 g, premature, and younger, are have a higher risk of developing LRLN palsy.…”
Section: Conditions Associated With Lrln Palsymentioning
confidence: 99%
“…3,4 It was also associated with double outlet right ventricle, 5 Ebstein's anomaly, 6 patent ductus arteriosus (PDA), 7 and Eisenmenger's complex. 8 Ductal ligation and transcatheter closure of PDA is associated with a risk of LRLN palsy. 9,10 Infants, who are less than 1500 g, premature, and younger, are have a higher risk of developing LRLN palsy.…”
Section: Conditions Associated With Lrln Palsymentioning
confidence: 99%
“…Although he attributed the hoarseness to paralysis of the left vocal cord due to compression of the left recurrent laryngeal nerve between the enlarged left atrium and the arch of the aorta, his explanation has been questioned by subsequent workers. According to a literature review, Sengupta et al 5 concluded that the etiology of left recurrent laryngeal nerve paralysis was compression of the nerve between the enlarged tense left pulmonary artery and the aorta at the ligamentum arteriosum. That is the reason why Ortner syndrome may also occur in primary pulmonary hypertension, Eisenmenger syndrome due to atrial septal defect where the left atrium is not enlarged, and even aortic aneurysms with encroachment of aorticopulmonary window and resultant compression of the left recurrent laryngeal nerve.…”
Section: To the Editormentioning
confidence: 99%
“…That is the reason why Ortner syndrome may also occur in primary pulmonary hypertension, Eisenmenger syndrome due to atrial septal defect where the left atrium is not enlarged, and even aortic aneurysms with encroachment of aorticopulmonary window and resultant compression of the left recurrent laryngeal nerve. 5 Finally, I wish to echo Hurst's teaching that a giant left atrium is more commonly associated with mitral regurgitation than mitral stenosis and rheumatic than nonrheumatic cause of mitral regurgitation. However, like everything in medicine, there may always be exceptions.…”
mentioning
confidence: 96%
“…The ascending and descending thoracic aortic walls were thickened to 5 mm. Laryngoscopy revealed paralysis of the left vocal fold consistent with pressure on the left branch of the recurrent laryngeal nerve (also known as Ortner's effect 3 ).…”
Section: To the Editormentioning
confidence: 97%